A Global Misuse of Semaglutide for Cosmetic Weight Loss in Non-diabetic Young Population, an FDA Public Database and Google Trends Data Analysis - Saber, Nahid Sabah aldin; AL-mihanya, Rawaq Haider (AL-Kindy College Medical Journal, 2025)
Background: in a world full of aesthetic trends and a pervasive focus on physical appearance, often driven by celebrities and social media influencers. The misuse of medications and increased demand on aesthetic surgeries have been documented and become increasingly concerning. Recently, the use of GLP-1 analog medications for aesthetic weight management, particularly Semaglutide (brand name Ozempic and Wegovy) has gained increasing popularity among the public on these platforms. Subjects and Methods: Our study aimed to investigate the potential for Semaglutide misuse, particularly Ozempic based on FAERS database and Google Trends tool. We also explored the potential adverse events associated with Semaglutide medication’s misuse. Results: Our findings showed a surge in Semaglutide medication (Ozempic) for weight loss as opposed to T2DM treatment worldwide. Moreover, Ozempic popularity for weight loss outweighs the popularity of Wegovy, which was approved for weight management indications in obese patients with at least one weight-related comorbidity. Furthermore, our results demonstrated an annual increase in the number of Semaglutide-related AERs on FAERS from January 2018 to September 2024, including a rise in death related AERs. A wide verity of Semaglutide related AERs have been documented, including both serious and non-serious outcomes, with death being the most serious outcome reported. Current results have also documented a worldwide shortage in Semaglutide medications, particularly Ozempic and Wegovy, due to increased demand and off-label use of these medications. Conclusion: collectively, our findings provide clear evidence of Ozempic and Wegovy misuse outside their approved indications to achieve aesthetic weight goals among young non-diabetic individuals. This misuse is often driven by media platforms without stressing on the potential adverse events and ethical concerns associated with the misuse of these medications.